Family and kin in Indo-European culture - Ghurye, G.S. (London, 1955)
Family and kin have excited the interest of students of civili zation for nearly a century in the modern period. The intrinsic appeal of the study of kinship pattern and familial organization is wider still. India with a very long and continuous social history has a distinct contribution to make to this study. Sir Henry Sumner Maine used some of the Indian material in his study of family in its comparative aspect. The integration of the data from the social histories of other peoples of Indo-European speech has also been appreciated. First, de Coulanges and Hearn and later Rivers and Sir Paul Vinogradoff made use of it: Rivers on the aspect of kin terminology and the others on the familial organization of the Indo-European peoples.
Keywords: Sociology